Principles of surgical treatment of congenital, developmental and acquired female breast asymmetries - Novaković Marijan; Lukač Marija; Kozarski Jefta; Stepić Nenad; Đorđević Boban; Vulović Dejan; Rajović Milica; Milev Boško; Milićević Saša (Vojnosanitetski Pregled)
Background/Aim. There is a natural asymmetry in normal female brests. When the difference in the shape, size or position of the breast and nipple-areola complex is visible, surgical correction is the only treatment option and presents one of the greatest challenges for a plastic surgeon. Based on the Nahai classification presented in details, the aim of the study was to present the possibilities of plastic surgery to correct primary (congenital), secondary (developmental) and tertiary (acquired) brest asymmetries. Methods. We conducted a retrospective analysis of female breast asymmetry surgeries performed in the Clinic for Plastic Surgery and Burns, Military Medical Academy (MMA), Belgrade over the last seven years (January 2002 - January 2009). Results. During the above mentioned period, 82 female patients, 18 - 65 years of age, underwent surgery for breast asymmetry. The most frequent asymmetries were developmental, 'pubertal' (n = 43); acquired asymmetries as a consequence of tumor surgery were found in the other 22 patients, while 7 patients were diagnosed with primary asymmetries such as congenital chest-wall asymmetry (Sy. Poland), accessory and tuberous breasts. All patients underwent preoperative ultrasound examination, while hormone status was determined in those with developmental, 'pubertal' asymmetries. The selection of surgical procedure for correction of breast asymmetry depended upon clinical examination findings and patient's wish relating to the shape and size of the breasts. The most of breast asymmetries were corrected by a combination of surgical procedures including primary and secondary reconstruction, reduction, suspension or augmentation mammoplasty. Having combined different surgical procedures, we managed to achieve satisfactory results. The hypertrophic scar formation after reduction mamoplasty was seen in some cases, however, they caused no significant patient's discomfort. Conclusion. Application of plastic, reconstructive and aesthetic surgical principles can considerably contribute to achieving excellent results in corrective surgery for breast asymmetries. In addition to most suitable breast asymmetry surgical procedures choice, motivation of a patient is also very important for achieving satisfactory results.